Tuning the Coupling in Single‐Molecule Heterostructures: DNA‐Programmed and Reconfigurable Carbon Nanotube‐Based Nanohybrids. Issue 10 (14th August 2018) - Freeley, Mark; Attanzio, Antonio; Cecconello, Alessandro; Amoroso, Giuseppe; Clement, Pierrick; Fernandez, Gustavo; Gesuele, Felice; Palma, Matteo
Abstract: Herein a strategy is presented for the assembly of both static and stimuli‐responsive single‐molecule heterostructures, where the distance and electronic coupling between an individual functional nanomoiety and a carbon nanostructure are tuned via the use of DNA linkers. As proof of concept, the formation of 1:1 nanohybrids is controlled, where single quantum dots (QDs) are tethered to the ends of individual carbon nanotubes (CNTs) in solution with DNA interconnects of different lengths. Photoluminescence investigations—both in solution and at the single‐hybrid level—demonstrate the electronic coupling between the two nanostructures; notably this is observed to progressively scale, with charge transfer becoming the dominant process as the linkers length is reduced. Additionally, stimuli‐responsive CNT‐QD nanohybrids are assembled, where the distance and hence the electronic coupling between an individual CNT and a single QD are dynamically modulated via the addition and removal of potassium (K + ) cations; the system is further found to be sensitive to K + concentrations from 1 pM to 25 × 10 −3 m . The level of control demonstrated here in modulating the electronic coupling of reconfigurable single‐molecule heterostructures, comprising an individual functional nanomoiety and a carbon nanoelectrode, is of importance for the development of tunable molecular optoelectronic systems and devices. Abstract : A strategy is presented for the assembly of static and stimuli‐responsive single‐molecule heterostructures : the distance and electronic coupling between an individual functional nanomoiety and a carbon nanostructure are tuned via the use of DNA linkers. The level of control demonstrated here in the assembly of reconfigurable single‐molecule heterostructures is key for the development of tunable molecular optoelectronic systems and devices.